Effect of Cricoid Pressure on Laryngeal View During Macintosh, McGrath MAC X-Blade and GlideScope Video Laryngoscopies - Arslan, Zehra İpek (Turk J Anaesthesiol Reanim, 2017)
OBJECTIVE: Cricoid pressure is useful in fasted patients requiring emergency intubation. We compared the effect of cricoid pressure on laryngeal view during Macintosh, McGrath MAC X-Blade and GlideScope video laryngoscopy. METHODS: After obtaining approval from the Human Research Ethics Committee and written informed consent from patients, we enrolled 120 patients (American Society of Anesthesiologists I–II, age 18–65 years) undergoing elective surgery that required endotracheal intubation in this prospective randomised study. Patients were divided into three groups (Macintosh, McGrath MAC X-Blade and GlideScope). RESULTS: Demographic and airway variables were similar in the groups. Cormack-Lehane grades were improved or unchanged on using cricoid pressure in Macintosh and McGrath MAC X-Blade groups. However, laryngeal views worsened in 12 patients (30%), remained unchanged in 26 patients (65%) and improved in 2 patients (5%) in the GlideScope group (p<0.001). Insertion and intubation times for Macintosh and McGrath MAC X-Blade video laryngoscopes were similar. Insertion times for GlideScope and Macintosh video laryngoscopes were similar, but were longer than those for the McGrath MAC X-Blade video laryngoscope (p=0.02). Tracheal intubation took longer with the GlideScope video laryngoscope than with the other devices (p<0.001 and p=0.003). Mean arterial pressures after insertion increased significantly in Macintosh and GlideScope groups (p=0.004 and p=0.001, respectively) compared with post-induction values. Heart rates increased after insertion in all three groups compared with post-induction values (p<0.001). Need for optimisation manoeuvres and postoperative minor complications were comparable in all three groups. CONCLUSION: Although all three devices are useful for normal or difficult intubation, cricoid pressure improved Cormack-Lehane grades of Macintosh and McGrath MAC X-Blade video laryngoscopes but statistically significantly worsened that of the GlideScope video laryngoscope.